Case report: Clinical complete response in advanced ALK-positive lung squamous cell carcinoma: a case study of successful anti-PD-1 immunotherapy post ALK-TKIs failure - Yang, Chen; Zeng, Rui; Zha, Yawen; Li, Yani; Wang, Ting; Zhao, Ruolan; Li, Minying; Zhang, Jingjing (Frontiers in Immunology, 2024)
In patients with advanced lung adenocarcinoma (LADC) harboring the echinoderm microtubule-associated protein-like 4 (EML4) -anaplastic lymphoma kinase (ALK) rearrangement, targeted therapy typically demonstrates superior efficacy as an initial treatment compared to chemotherapy. Following resistance to ALK-tyrosine kinase inhibitors (TKIs), regimens incorporating platinum-based dual agents or combined with bevacizumab often show effectiveness. However, therapeutic alternatives become constrained after resistance develops to both TKIs and platinum-based therapies. Given that the majority of ALK-positive non-small cell lung carcinomas (NSCLC) are LADC, the benefits of TKIs for patients with ALK-positive lung squamous cell carcinoma (LSCC) and the optimal treatment strategy for these patients remain a subject of debate. In this case study, we report on a patient with advanced LSCC, in whom the EML4-ALK rearrangement was identified via ARMS-PCR (Amplification Refractory Mutation System-Polymerase Chain Reaction). The patient underwent oral treatment with crizotinib and alectinib, showing effectiveness in both first-line and second-line ALK-TKI therapies, albeit with limited progression-free survival (PFS). Subsequent resistance to second-generation TKI was followed by the detection of tumors in the left neck region via computed tomography (CT). Biopsy pathology revealed non-squamous cell carcinoma, and subsequent treatment with platinum-based double-drug therapy proved ineffective. Further analysis through next-generation sequencing (NGS) indicated ALK negativity but a high expression of programmed death-ligand 1 (PD-L1). Immunotherapy was then initiated, resulting in a PFS of over 29 months and clinical complete remission (cCR). This case underscores the potential benefit of ALK-TKIs in patients with ALK-positive LSCC.Resistance to second-generation TKIs may lead to ALK negativity and histological transformation, highlighting the necessity of repeated biopsies post-TKI resistance for informed treatment decision-making. As of November 2023, imaging studies continue to indicate cCR in the patient, with a survival time exceeding 47 months.